PENGARUH KUALITAS PELAYANANDAN PROMOSI TERHADAP LOYALITAS KONSUMEN PADA INOVA PRINTER CENTER BREBES - Lusia Wulandari Soetejo; Zeki Ade Saputra (Sekolah Tinggi Ilmu Ekonomi Widya Manggalia, 2022)
ABSTRACT This research takes the title Effect of Service Quality and Promotion on Consumer Loyalty at Inova Printer Center Brebes. This study aims to determine: 1. The effect of Service Quality and Promotion partially on Consumer Loyalty at the Inova Printer Center Brebes, 2. The influence of Service Quality and Promotion simultaneously on the Consumer Loyalty at the Inova Printer Center Brebes, 3. Which variable has the dominant influence towards Consumer Loyalty at Inova Printer Center Brebes. While the proposed hypothesis is: 1. Allegedly Quality of Service and Promotion partially affect Consumer Loyalty at Inova Printer Center Brebes, 2. Allegedly Quality of Service and Promotion have a simultaneous effect on Consumer Loyalty at Inova Printer Center Brebes, 3. Allegedly Quality of Service has a dominant influence on Consumer Loyalty at Inova Printer Brebes Center. This research is a quantitative research with survey method. The population in this case are customers who make transactions at Inova Printer Center Brebes. The sampling technique used purposive sampling with a total sample of 100 people. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used to answer the hypothesis is by regression analysis, t test and f test. The results of this study indicate that: 1. The statistical results of the t-test are based on a significant value of 0.023 <0.05 and a value of i????????????g 2.315 >???????????????????????? 1.984 so it can be concluded that 0 is rejected and is accepted, which means that the service quality variable (X1) affects the consumer loyalty variable ( Y). Based on the significant value of 0.122 <0.05 and the value of i????????????g 1.561 <???????????????????????? 1.984, it can be concluded that 0 is accepted and is rejected, which means that the promotion variable (X2) has no effect on the consumer loyalty variable (Y). 2. The resulting significance value is smaller than 0.05 or i????????????g>???????????????????????? = 7.411 > 3.09, so it can be concluded that there is a simultaneous effect of the independent variable of service quality and promotion (X) on the dependent variable of consumer loyalty (Y). 3. The dominant variable on consumer loyalty is service quality. This can be seen from the statistical results of the t test which states that service quality has a positive effect on consumer loyalty, while promotion has no effect on consumer loyalty.